EFEKTIVITAS KONSELING KELOMPOK DENGAN TEKNIK SELF-MANAGEMENT UNTUK MENINGKATKAN DISIPLIN BELAJAR PESERTA DIDIK - Ramadhani, Eliza Eka; Wicaksono, Luhur; Astuti, Indri (Universitas Tanjungpura, 2023)
This study discipline research aims to test the effectiveness of counseling groups with self-management techniques to improve learning discipline class VIII at SMP Negeri 1 Sungai Raya. Research methods that used is an experiment with the form of Pre-Experimental Design research with the research design One-Group Pretest-Posttest Design. Technique sampling using Nonprobability Sampling technique with types Purposive Sampling in which the samples were taken as many as 6 class VIII. The data collection technique uses a questionnaire with a Likert scale and tested the validity and reliability of the questionnaire. The results of the sub-problem research one and two, namely the level of learning discipline obtained before being given service group counseling with self-management techniques is 81.00 and after given service is 131.33. Furthermore, for the sub-problems three obtained value, that is sig. (2-tailed) 0.000 0.05 which means there is a significant difference significantly between the level of learning discipline of students before and after given group counseling with self-management techniques. So got it was concluded that group counseling with self-management techniques was effective to improve the learning discipline of class VIII at SMP Negeri 1 Sungai Raya.